2021
DOI: 10.1038/s41598-021-96505-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic cholinergic stimulation associated with aerobic physical training on cardiac morphofunctional and autonomic parameters in spontaneously hypertensive rats

Abstract: We investigated hemodynamic, cardiac morphofunctional, and cardiovascular autonomic adaptations in spontaneously hypertensive rats (SHRs) after aerobic physical training associated with chronic cholinergic stimulation. Fifty-four SHRs were divided into two groups: trained and untrained. Each group was further subdivided into three smaller groups: vehicle, treated with pyridostigmine bromide at 5 mg/kg/day, and treated with pyridostigmine bromide at 15 mg/kg/day. The following protocols were assessed: echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It has been shown that use of acetylcholine esterase inhibitors is associated with increasing the concentration of acetylcholine both in the synaptic cleft in the neuromuscular junction and in synapses of CNS and autonomic ganglia. Experimental evidence indicates that pyridostygmine improves the autonomic profile, reduces HR at rest, and enhances short-term HRV [38][39][40]. A previous study in spontaneously hypertensive rats showed that cholinergic stimulation with pyridostigmine bromide for 2 weeks reduced BP, HR as well as increased vagal participation in autonomic balance and decreased systolic BPV [38].…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that use of acetylcholine esterase inhibitors is associated with increasing the concentration of acetylcholine both in the synaptic cleft in the neuromuscular junction and in synapses of CNS and autonomic ganglia. Experimental evidence indicates that pyridostygmine improves the autonomic profile, reduces HR at rest, and enhances short-term HRV [38][39][40]. A previous study in spontaneously hypertensive rats showed that cholinergic stimulation with pyridostigmine bromide for 2 weeks reduced BP, HR as well as increased vagal participation in autonomic balance and decreased systolic BPV [38].…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence of autonomic involvement in individuals with MG [ 6 , 15 ] before and after pharmacological treatment. Cholinergic stimulation induced by AChE inhibitor treatment influences autonomic function, including cardiac function, and improves BRS and HRV in both humans and animal disease models [ 35 , 36 ]. AChE inhibitors also increase the HF while decreasing the LF and sympathovagal balance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the prolonged use of pyridostigmine enhances cardiac autonomic control, including improvements in vagal tone, BRS, and HRV. In our previous study, we established the presence of diminished cardiovagal tone in MG patients, even as the acetylcholinesterase inhibitors led to an enhancement in vagal tone [17,49]. Considering the evaluation of HRV, future studies could focus on establishing stable therapies for MG before conducting the assessment, maintaining no dose changes for at least 3 months (e.g., corticosteroids).…”
Section: Discussionmentioning
confidence: 99%